FROM MODERNISM TOWARDS POST-MODERNIOSM – RATIONALISM AND THE ENLIGHTNMENT ERA (Baština, 2020)
Modernism and post-modernism are predestined to have a common denominator. Spiritual precursors of post-modernism appear with the development of rationalism and the enlightenment era. It will have proven later on that post-modernists wished to impose themselves as a total opposition to modernism, but they could not avoid the fact that post-modernism originated from modernism. In the oeuvres of post-modernists it is woven the social and philosophical thought of Bacon, Descartes, Locke, Hume, Voltaire and later on, Heidegger, Nietzsche, Wittgenstein and Weber, which shortened the way from modernism toward post-modernism. Independently of the fact whether they are for inductive and deductive method of research, empirists started doubting in the supreme value of reason, and they gave some importance to language and text including the anti-historicity. Post-modernists turned the comprehensions of modernists upside down so as to reveal rational core in that mystical envelope. In the measure in which reason was taking win over faith and mysticism, in the same measure post-modernism was replacing modernism, but not with the aim to eliminate it but to give some modernistic categories a new quality.
Keywords: Modernism, post-modernism, empirism, rationalism, enlightenment era, precursors.